EFFECTIVENESS OF USING SPIRULINA IN CONJUNCTION WITH ARTEMISININ COMBINATION THERAPY AS AN ANTIMALARIAL TREATMENT - ASSEGAF, NAJMA; ASTUTY, HENDRI (International Journal of Applied Pharmaceutics, 2019)
Objective: This study investigated whether the herbal plant Spirulina could be used in crude form as an alternative therapy to artemisinin combination therapy (ACT) for the treatment of malaria caused by Plasmodium falciparum. Methods: Mice infected by Plasmodium berghei were treated orally with a single dose of Spirulina (200 or 400 mg/kg body weight [BW]), dihydroartemisinin-piperaquine as a type of ACT, or a combination of the two. The level of parasitemia was then compared between the groups during the 4-day post-infection period. Results: There was a significant difference in the change in the level of parasitemia from day 0 to day 4 between groups (Kruskal–Wallis test, P < 0.05). Mice that were treated with both doses of Spirulina alone had a significantly higher parasitemia density than those treated with ACT alone. However, the combination of Spirulina and ACT had a synergistic effect, with 200 mg/kg BW Spirulina + ACT giving significantly better results than ACT alone. Conclusion: These findings indicate that treatment with Spirulina alone cannot be used as antimalarial medication, but its combination with ACT can lead to enhanced antimalarial activity.